Effect of transition metal on stability and activity of La-Ca-M-(Al)-O (M = Co, Cr, Fe and Mn) perovskite oxides during partial oxidation of methane. (3rd August 2017) - Cihlar, Jaroslav; Vrba, Radimir; Castkova, Klara; Cihlar, Jaroslav
Abstract: Perovskite oxides of the type of Lax Ca1-x My Al1-y O3-δ (M = Co, Cr, Fe, Mn; x = 0.5; y = 0.7–1.0) were prepared using the polymerization methods and evaluated via N2 adsorption, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning transmission electron microscopy (STEM), energy dispersive X-ray (EDX) spectroscopy, temperature-programmed reduction by hydrogen (TPR-H2 ) and temperature-programmed oxidation by oxygen (TPO-O2 ). Catalytic behaviour of the perovskite oxides during methane oxidation was studied using a tubular fixed-bed reactor. In a partial oxidation, which proceeded in two steps, there was total oxidation in the first step and CO2 and H2 O were formed; in the second step, the total oxidation products oxidized methane by (dry and wet) reforming reactions to yield CO and H2 . Total oxidation and the two reforming reactions proceeded on two types of an active centre formed by transition metal ions, oxygen vacancies and oxide ions. The catalytic system La-Ca-Co-Al-O which contained aluminium, decomposed in partial oxidation of methane (POM) into a composite that contained firmly bonded cobalt nanoparticles in the surface of a substrate made up of La2 O3, CaO and Al2 O3 which catalysed POM with a high methane conversion and hydrogen selectivity. Graphical abstract: Highlights: Redox stability of the La-Ca-M-(Al)-O (M = Co, Cr, Fe and Mn) perovskites. Partial oxidation of methane by perovskites takes place in two steps. Decomposition products of La-Ca-M-(Al)-O (M = Co, Fe) show highest catalytic activity. Aluminium doping of perovskites in most cases increases their catalytic activity.